Analisis dan Ekspresi Gerak: Mencari Hubungan Pada “Sonata Romantica Bagain I. Allegro Moderato” Manuel Ponce - Leonard Aldo Prasetyo Sembiring (Virtuoso: Jurnal Pengkajian dan Penciptaan Musik, 2022)
This research departs from the difficulty of players in connecting how musical works can inform movements to players, he said on classical guitarist instruments. So it requires a strategy to answer the challenges in the music performance area. So this study requires several processes to connect this, one of which is the positive analysis that will be discussed in this research. The discussion material is limited to romantic to modern music as a golden era of classical guitar, one of which is the work of Manuel Maria Ponce's "Sonata Romantica I. Allegro Moderato". The content of this study is in the form of a study of elements of music elements including; harmonic studies, forms, rhythms and motifs, as well as looking at the results of other players in interpreting the work.  While the results of this study show that there are many fluctuations in the two regions of the graph representing dynamic and tempo, it is from these fluctuations that musicians get the potential to use gesture expressions.